Enhancement of glycerol conversion to acetol in high-temperature liquid water by high-pressure carbon dioxide - Yamaguchi, Aritomo; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2008)
Dehydration of glycerol to acetol proceeded in high-temperature liquid water at 573 K in a batch reactor. The acetol formation rate increased with an addition of high-pressure carbon dioxide.